Carbon ceramic product and preparation method thereof, and transportation vehicle
During the preparation process of carbon ceramic products, the problem of insufficient impact toughness of traditional short fiber carbon ceramic brake discs is solved, and the high impact toughness and tensile strength are improved.
Patent Information
- Application Number
- CN202411834281.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-13
AI Technical Summary
The impact toughness of traditional short fiber carbon ceramic brake discs is poor and it is difficult to meet the needs of high-performance braking systems.
By mixing carbon powder, metal oxide, binder and additives for intensive refining or kneading, intermediate mixture is prepared, and then mixed with chopped carbon fibers, molding, carbonization and silicone permeation treatment, carbonaceous products with high impact toughness and tensile strength are prepared.
It improves the impact toughness and tensile strength of carbon ceramic products, while ensuring its bending strength and compression strength, meeting the needs of high-performance brake discs.
Smart Images

Figure CN119285362B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of materials, and in particular to a carbon ceramic product and a preparation method thereof, and a means of transportation. Background Art
[0002] Carbon ceramic brake disc is a kind of brake disc made of carbon fiber reinforced silicon carbide composite material. It is the third generation of brake material developed after powder metallurgy brake disc. Compared with traditional powder metallurgy brake disc, it has low density, high strength, high temperature resistance, impact resistance, good thermal conductivity, oxidation resistance and stable friction coefficient. It is an ideal friction material and is widely used in aerospace and high-speed rail braking systems.
[0003] Carbon ceramic brake discs are mainly divided into two types: long fiber discs and short fiber discs. Compared with long fiber discs, short fiber discs have the advantages of short preparation cycle and low cost. However, the impact toughness of traditional short fiber discs is poor.
[0004] Therefore, it is necessary to improve the traditional technology. Summary of the invention
[0005] Based on this, the present application provides a carbon ceramic product with good impact toughness, a preparation method thereof, and a means of transportation.
[0006] The technical solution of this application to solve the above technical problems is as follows.
[0007] The first aspect of the present application provides a method for preparing a carbon ceramic product, comprising the following steps:
[0008] The carbon powder, the metal oxide, the binder and the additive are mixed and kneaded to prepare an intermediate mixture;
[0009] Mixing the chopped carbon fibers with the intermediate mixture to prepare a carbon fiber mixture;
[0010] The carbon fiber mixture is subjected to molding treatment, carbonization treatment and siliconization treatment in sequence to prepare a carbon ceramic product.
[0011] In some of the embodiments, in the method for preparing the carbon ceramic product, the kneading temperature is 60° C. to 80° C., and the time is 10 min to 30 min.
[0012] In some of the embodiments, in the method for preparing the carbon ceramic product, the kneading temperature is 120° C. to 150° C., and the kneading time is 30 min to 120 min.
[0013] In some of the embodiments, in the method for preparing the carbon ceramic product, in the step of mixing the chopped carbon fibers with the intermediate mixture, the mixing temperature is 20° C. to 35° C., and the stirring speed is 10 r / min to 30 r / min.
[0014] In some of the embodiments, in the method for preparing the carbon ceramic product, the mass ratio of the binder, the carbon powder, the additive and the metal oxide is 25-35:10-30:3-5:0.5-2.
[0015] In some of the embodiments, in the method for preparing the carbon ceramic product, the mass ratio of the chopped carbon fibers to the intermediate mixture is 0.5-1.5:1.
[0016] In some embodiments, in the method for preparing the carbon ceramic product, the preparation method satisfies at least one of the following characteristics:
[0017] (1) The binder includes at least one of solid phenolic resin, asphalt and liquid resin;
[0018] (2) The metal oxide includes at least one of aluminum oxide, yttrium oxide and zirconium oxide;
[0019] (3) The additive includes a pore-forming agent; optionally, the pore-forming agent includes at least one of ethylene glycol, PVB and plant fiber powder.
[0020] In some embodiments, in the method for preparing the carbon ceramic product, the preparation method satisfies at least one of the following characteristics:
[0021] (1) The temperature of the molding process is 120°C to 200°C, the pressure of the molding process is 100 to 150 tons, and the holding time of the molding process is 20 min to 40 min;
[0022] (2) The temperature of the carbonization treatment is 1000°C to 1200°C, and the time of the carbonization treatment is 50 h to 70 h.
[0023] (3) The temperature of the siliconizing treatment is 1500°C to 1700°C, and the time of the siliconizing treatment is 3 h to 5 h;
[0024] (4) The siliconizing treatment comprises: placing silicon sources on the upper surface and the lower surface of the carburized body after the carbonization treatment, respectively, and performing the siliconizing treatment in a siliconizing furnace;
[0025] Optionally, the silicon source includes silicon alone.
[0026] A second aspect of the present application provides a carbon ceramic product, which is prepared using the above-mentioned method for preparing the carbon ceramic product.
[0027] In some embodiments, the carbon-ceramic article includes a carbon-ceramic brake rotor.
[0028] A third aspect of the present application provides a means of transportation, comprising the above-mentioned carbon ceramic product.
[0029] Compared with the prior art, the preparation method of the carbon ceramic product of the present application has the following beneficial effects:
[0030] The preparation method of the carbon ceramic product of the present application first mixes carbon powder, metal oxide, binder and additives for internal mixing or kneading, and the binder is evenly coated on the surface of powder raw materials such as carbon powder, which can avoid the problem of agglomeration of powder raw materials such as carbon powder and the binder; then the prepared intermediate mixture is mixed with chopped carbon fibers, and the binder coated on the surface of the powder has good bonding performance with the chopped carbon fibers, which can effectively improve the bonding force between the chopped carbon fibers and the powder, and avoid stratification of the powder and the chopped carbon fibers, thereby improving the uniformity of the embryo obtained by the molding treatment, and then improving the impact toughness and tensile strength of the carbon ceramic product obtained by the carbonization treatment and siliconization treatment, while ensuring that the bending strength and compression strength of the carbon ceramic product are also high. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0032] Figure 1 The metallographic image of the finished carbon ceramic disc prepared in Example 1;
[0033] Figure 2 The metallographic image of the finished carbon ceramic disc prepared in Example 3;
[0034] Figure 3 The metallographic image of the finished carbon ceramic disc prepared in Example 4;
[0035] Figure 4 This is a metallographic image of the finished carbon ceramic disc prepared in Comparative Example 1;
[0036] Figure 5 This is a metallographic image of the finished carbon ceramic disc prepared in Comparative Example 2;
[0037] Figure 6 This is the metallographic image of the finished carbon ceramic disc prepared in Comparative Example 3. DETAILED DESCRIPTION
[0038] References to embodiments of the present invention will now be provided in detail, one or more examples of which are described below. Each example is provided as an explanation rather than a limitation of the present invention. In fact, it will be apparent to those skilled in the art that various modifications and variations may be made to the present invention without departing from the scope or spirit of the present invention. For example, a feature illustrated or described as part of one embodiment may be used in another embodiment to produce a further embodiment.
[0039] Therefore, it is intended that the present invention covers such modifications and variations that fall within the scope of the appended claims and their equivalents. Other objects, features and aspects of the present invention are disclosed in or are obvious from the following detailed description. Those of ordinary skill in the art will appreciate that this discussion is only a description of exemplary embodiments and is not intended to limit the broader aspects of the present invention.
[0040] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0041] The term "comprises", "comprising" or any other variant thereof is intended to cover non-exclusive inclusion, so that the process, method, article or equipment including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment. In the absence of more restrictions, the elements defined by the sentence "comprising one..." do not exclude the presence of other identical elements in the process, method, article or equipment including the elements. The indefinite articles "a kind of" and "an" before the elements or components of the present invention are not restrictive to the quantity requirements (i.e., the number of occurrences) of the elements or components. Therefore, "a" or "a kind of" should be interpreted as including one or at least one, and the elements or components in the singular form also include the plural form, unless the number clearly refers only to the singular form. The meaning of "multiple" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0042] The weight of the relevant components mentioned in the description of the embodiments of the present invention may not only refer to the specific content of each component, but also indicate the weight ratio between the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the description of the embodiments of the present invention, it is within the scope disclosed in the description of the embodiments of the present invention. Specifically, the weight described in the description of the embodiments of the present invention may be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.
[0043] Except as shown in the operating examples or otherwise indicated, all numbers used in the specification and claims to indicate the amount of ingredients, physicochemical properties, etc. are understood to be adjusted by the term "about" in all cases. For example, therefore, unless otherwise indicated, the numerical parameters listed in the above specification and the attached claims are approximate values, and those skilled in the art can use the teachings disclosed herein to seek to obtain the desired properties and appropriately change these approximate values. The use of numerical ranges expressed as endpoints includes all numbers within the range and any range within the range, for example, 1 to 5 includes 1, 1.1, 1.3, 1.5, 2, 2.75, 3, 3.80, 4 and 5, etc.
[0044] The analysis shows that the density of carbon fiber and other powders such as resin and carbon powder is quite different. Resin and carbon powder agglomeration and material stratification are likely to occur in the mixed materials, resulting in large differences in performance in different areas. Lack of resin in local areas can easily lead to defective products. After carbonization and siliconization, the fiber reinforcement phase and silicon carbide matrix are unevenly distributed. The impact toughness and tensile strength of the silicon carbide matrix are relatively low, resulting in lower overall brake disc performance or unqualified products.
[0045] An embodiment of the present application provides a method for preparing a carbon ceramic product, comprising the following steps:
[0046] Step S10: mixing the carbon powder, metal oxide, binder and additives, and kneading or mixing them to prepare an intermediate mixture.
[0047] In some of the examples, in step S10, the mass ratio of the binder, the carbon powder, the additive and the metal oxide is 25-35:10-30:3-5:0.5-2.
[0048] It can be understood that the mass ratio of binder to carbon powder is 25~35:10~30; the mass ratio of additive to carbon powder is 3~5:10~30; and the mass ratio of metal oxide to carbon powder is 0.5~2:10~30.
[0049] Optionally, the mass ratio of the binder, carbon powder, additive and metal oxide is 25-30:15-20:3-4:1-2.
[0050] Furthermore, the mass ratio of the binder, carbon powder, additive and metal oxide is 28~30:18~20:3~4:1~2.
[0051] In some examples, in step S10 , the binder includes at least one of solid phenolic resin, asphalt, and liquid resin.
[0052] In some examples, in step S10 , the metal oxide includes at least one of aluminum oxide, yttrium oxide, and zirconium oxide.
[0053] In some examples, in step S10 , the additive includes a pore former.
[0054] Furthermore, the pore-forming agent includes but is not limited to at least one of ethylene glycol, PVB and plant fiber powder.
[0055] It can be understood that step S10 includes step S11 or step S12:
[0056] Step S11: mixing carbon powder, metal oxide, binder and additives and kneading them to prepare an intermediate mixture.
[0057] In some of the examples, in step S11, the kneading temperature is 60° C. to 80° C., and the kneading time is 10 min to 30 min.
[0058] It can be understood that the temperature of the internal mixing refers to the set temperature of the internal mixer; further, the temperature of the internal mixing includes but is not limited to 60°C, 62°C, 65°C, 68°C, 70°C, 72°C, 75°C, 78°C, 80°C, and the time includes but is not limited to 10min, 12min, 15min, 18min, 20min, 22min, 25min, 28min, 30min. In some examples, any two of these point values can be used as end values within the range, the same below.
[0059] In some examples, in step S11 , the binder includes solid phenolic resin.
[0060] In some of the examples, in step S11, a three-dimensional mixer is used to mix the carbon powder, the metal oxide, the binder and the additive.
[0061] In some examples, after step S11 is completed and before step S20, the process further includes crushing the intermediate mixture prepared in step S11. Further, the particle size of the crushed intermediate mixture is 3 mm to 5 mm.
[0062] Step S12: mixing and kneading the carbon powder, metal oxide, binder and additive to prepare an intermediate mixture.
[0063] It can be understood that in step S12, the binder is a liquid binder. Further, the liquid binder includes at least one of asphalt and liquid resin. Further, the liquid resin includes liquid phenolic resin. Further, the binder includes asphalt.
[0064] In some of the examples, in step S12, the kneading temperature is 120° C. to 150° C., and the kneading time is 30 min to 120 min.
[0065] It can be understood that the kneading temperature refers to the set temperature of the kneading machine; further, the kneading temperature includes but is not limited to 120°C, 130°C, 140°C, 150°C, and the time includes but is not limited to 30min, 50min, 80min, 100min, 120min.
[0066] In some examples, step S12 includes step S121: preheating the carbon powder, metal oxide and additives, and then mixing the preheated mixture with a liquid binder for kneading.
[0067] In some of the examples, in step S121, carbon powder, metal oxide and additives are placed in a kneading machine for preheating and kneading, and then a liquid binder is added for kneading.
[0068] In some examples, step S12 includes step S122:
[0069] The carbon powder, metal oxide and additive are mixed and preheated, and then the preheated mixture is mixed with asphalt for kneading.
[0070] In some of the examples, in step S122, carbon powder, metal oxide and additives are placed in a kneading machine for preheating and kneading, and then liquid asphalt is added for kneading.
[0071] In some of the examples, in step S122, the setting temperature of the kneading machine is 140°C to 150°C, and the preheating kneading time is 40min to 80min.
[0072] It will be appreciated that liquid asphalt may be melted by subjecting the asphalt to a temperature above its melting point.
[0073] In some of the examples, step S12 includes step S123:
[0074] The carbon powder, metal oxide and additive are mixed and preheated, and then the mixed material obtained by the preheating is mixed with the liquid phenolic resin for kneading.
[0075] In some of the examples, in step S123, the carbon powder, metal oxide and additive are placed in a kneading machine for preheating and kneading, and then the liquid phenolic resin is added and kneaded.
[0076] Furthermore, in step S123, the setting temperature of the kneading machine is 60°C to 80°C, and the preheating kneading time is 20min to 40min.
[0077] Step S20: Mixing the chopped carbon fibers with the intermediate mixture to prepare a carbon fiber mixture.
[0078] In some of the examples, in step S20, the mass ratio of the chopped carbon fibers to the intermediate mixture is 0.5-1.5:1.
[0079] It can be understood that the mass ratio of chopped carbon fiber to intermediate mixture includes but is not limited to 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, and 1.5:1.
[0080] Optionally, in step S20, the mass ratio of the chopped carbon fibers to the intermediate mixture is 1-1.5:1.
[0081] In some of the examples, in step S20, the mixing temperature is 20°C to 35°C, and the stirring speed is 10 r / min to 30 r / min.
[0082] It will be appreciated that the mixing is carried out at room temperature, and the stirring speed includes but is not limited to 10 r / min, 12 r / min, 15 r / min, 18 r / min, 20 r / min, 22 r / min, 25 r / min, 28 r / min, and 30 r / min.
[0083] In some examples, in step S20, stirring and mixing is performed in a high-speed mixer.
[0084] In some of the examples, in step S20, the length of the chopped carbon fibers is 8 mm to 15 mm.
[0085] It is understood that the length of the chopped carbon fibers includes, but is not limited to, 8 mm, 9 mm, 10 mm, 11 mm, 12 mm, 13 mm, 14 mm, and 15 mm.
[0086] In some of the examples, in step S20, a modified material is provided on the side of the chopped carbon fiber, and the modified material includes at least one of polyurethane and epoxy resin.
[0087] In some examples, in step S20, the preparation of chopped carbon fibers includes the following steps:
[0088] The carbon fibers are first compressed and bundled, and then chopped after the surface is sizing and solidified.
[0089] Optionally, the sizing includes at least one of a polyurethane solution and an epoxy resin solution.
[0090] Furthermore, the mass concentrations of the polyurethane solution and the epoxy resin solution are independently 2% to 5%.
[0091] It can be understood that the mass concentrations of the polyurethane solution and the epoxy resin solution independently include but are not limited to 2%, 3%, 4%, and 5%.
[0092] Optionally, the carbon fiber includes but is not limited to T700 carbon fiber; further, the carbon fiber includes 24k or 12k.
[0093] Step S30: subjecting the carbon fiber mixture to molding, carbonization and siliconization treatments in sequence to prepare a carbon ceramic product.
[0094] By first mixing the carbon powder, metal oxide, binder and additives and performing internal kneading or mixing, the binder is evenly coated on the surface of powder raw materials such as carbon powder, which can avoid the problem of agglomeration of powder raw materials such as carbon powder and the binder; the prepared intermediate mixture is then mixed with chopped carbon fibers, and the binder coated on the surface of the powder has good bonding performance with the chopped carbon fibers, which can effectively improve the bonding force between the chopped carbon fibers and the powder, and avoid stratification of the powder and the chopped carbon fibers, thereby improving the uniformity of the embryo obtained by the molding treatment, and then improving the impact toughness and tensile strength of the carbon ceramic products obtained by carbonization and siliconization treatment, while ensuring that the bending strength and compression strength of the carbon ceramic products are also high.
[0095] If chopped carbon fibers are mixed or kneaded together with carbon powder, metal oxides, binders and additives, the improvement in tensile strength and impact toughness will be very limited. Analysis shows that the chopped carbon fibers are damaged during the mixing or kneading process.
[0096] It can be understood that the molding process forms a green body, the carbonization process forms a carbonized green body, and the siliconization process forms a carbon ceramic material.
[0097] In some of the examples, in step S30, the temperature of the molding process is 120°C to 200°C.
[0098] In some of the examples, in step S30, the pressure of the molding process is 100-150 tons.
[0099] In some of the examples, in step S30, the holding time of the molding process is 20 min to 40 min.
[0100] It will be understood that the temperature of the molding process includes but is not limited to 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, and 200°C; the pressure of the molding process includes but is not limited to 100 tons, 110 tons, 120 tons, 130 tons, 140 tons, and 150 tons; and the holding time of the molding process includes but is not limited to 20 min, 22 min, 25 min, 28 min, 30 min, 32 min, 35 min, 38 min, and 40 min.
[0101] In some of the examples, in step S30 , compression molding is performed under a flat vulcanizing press.
[0102] It can be understood that step S30 in the molding process includes first preparing a blank and then processing the blank into a desired shape. For example, when the prepared carbon ceramic product is a carbon ceramic brake disc, it is processed into the basic shape of a carbon ceramic brake disc.
[0103] Processing the blank into the brake disc shape is more convenient, more efficient and less costly than processing the silicon carbide blank.
[0104] In some examples, in step S30, the density of the embryo formed by the molding process is 1.25 g / cm 3 ~1.5 g / cm 3 .
[0105] In some of the examples, in step S30, the temperature of the carbonization treatment is 1000° C. to 1200° C., and the time of the carbonization treatment is 50 h to 70 h.
[0106] In some of the examples, in step S30, the temperature of the siliconizing treatment is 1500° C. to 1700° C., and the time of the siliconizing treatment is 3 h to 6 h.
[0107] It can be understood that the temperature of the siliconizing treatment includes but is not limited to 1500℃, 1520℃, 1550℃, 1580℃, 1600℃, 1620℃, 1650℃, 1680℃, and 1700℃, and the time of the siliconizing treatment includes but is not limited to 3 h, 3.5 h, 4 h, 4.5 h, 5 h, 5.5 h, and 6 h.
[0108] In some of the examples, in step S30, in the siliconizing step, the mass ratio of silicon to the carbonized body after the carbonization treatment is 1.2-1.8:1.
[0109] It can be understood that the mass ratio of the amount of silicon to the carbonized body after carbonization treatment includes but is not limited to 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, and 1.8:1.
[0110] In some of the examples, in step S30, in the siliconizing treatment step, silicon is placed on the upper surface and the lower surface of the carbide blank, and the mass ratio of the silicon on the upper surface to the silicon on the lower surface is 1:2-4.
[0111] In some of the examples, in step S30, the siliconizing treatment includes: placing silicon sources on the upper surface and the lower surface of the carburized body after the carbonization treatment, respectively, and performing the siliconizing treatment in a siliconizing furnace.
[0112] Optionally, the silicon source includes but is not limited to silicon alone.
[0113] In some examples, in step S30, the siliconizing treatment includes the following steps:
[0114] The carbide body is placed in a siliconizing tool, the surface of the tool is coated with boron nitride powder, a piece of graphite paper is added between the tool and the carbide body, silicon is added to the upper and lower surfaces of the carbide body, and the body is placed in a siliconizing furnace for siliconizing treatment.
[0115] It can be understood that coating the surface of the tooling with boron nitride powder is beneficial to protecting the tooling and reducing the corrosion of silicon to the tooling.
[0116] In some of the examples, after step S30 is completed, a step of providing a protective coating on the surface of the workpiece after the siliconizing treatment is also included.
[0117] It is understood that the protective coating includes but is not limited to anti-oxidation coating, anti-corrosion coating, etc.
[0118] In some of these examples, providing a protective coating on a siliconized workpiece surface includes the following steps:
[0119] The workpiece after siliconizing treatment is immersed in a protective solution and then sintered to form a protective coating on the surface of the workpiece.
[0120] In some examples, the protective solution includes, but is not limited to, at least one of aluminum dihydrogen phosphate, aluminum chromium phosphate, boric acid, zirconium, nickel, strontium, copper, and the like.
[0121] Applying an anti-oxidation coating on the surface of the workpiece after siliconizing treatment can prevent oxygen from reacting with carbon, silicon and fiber, thereby increasing the life of the brake disc at a low cost.
[0122] In some of these examples, the sintering temperature is 200°C to 300°C.
[0123] Some of the examples further include a step of finishing the workpiece after siliconizing treatment or after providing a protective coating.
[0124] Among them, finishing includes polishing the disc surface, through-hole drilling, etc.
[0125] An embodiment of the present application provides a carbon ceramic product, which is prepared by the above-mentioned method for preparing the carbon ceramic product.
[0126] The carbon ceramic product prepared by the preparation method of the carbon ceramic product has high impact toughness and tensile strength, and also high bending strength and compression strength.
[0127] It will be appreciated that carbon ceramic products include, but are not limited to, brake discs.
[0128] It can be understood that one embodiment of the present application provides a carbon-ceramic brake disc, which is manufactured using the above-mentioned method for preparing carbon-ceramic products.
[0129] The carbon ceramic brake disc prepared by the preparation method of the carbon ceramic product has high impact toughness and tensile strength, as well as high bending strength and compression strength, good thermal conductivity, excellent thermal shock resistance and stable friction performance.
[0130] An embodiment of the present application also provides a vehicle, comprising the above-mentioned carbon-ceramic brake disc.
[0131] It will be appreciated that vehicles include but are not limited to cars.
[0132] The present application is further described in detail below in conjunction with specific implementation methods, but the implementation methods of the present application are not limited thereto.
[0133] Example 1
[0134] S1. Premix the binder (solid phenolic resin), carbon powder, pore-forming agent (PVB) and metal oxide (aluminum oxide and yttrium oxide in a mass ratio of 1:1) in a mass ratio of 25:20:3:2, and mix them in an internal mixer. The mixing temperature (the setting temperature of the internal mixer) is 60°C, and the speed is 10 r / min~30 r / min. Mix them until the mixing temperature is higher than 85°C (about 15 min), discharge the materials, crush them, and sieve them through a 40-mesh screen to obtain an intermediate mixture;
[0135] S2, chopped carbon fiber (12K T700 grade sizing carbon fiber, the slurry is a PU solution with a solid content of 2% to 4%, and the length is 8 mm) and the intermediate mixture prepared in step S1 are mixed uniformly in a high-speed mixer at a mass ratio of 1:1, and the speed is 20 r / min at room temperature to obtain a carbon fiber mixture;
[0136] S3, compression molding: put the carbon fiber mixture prepared in step S2 into the mold to make it evenly distributed in the mold, cover the mold cover plate, place it in a flat vulcanizer with a pressing pressure of 200 tons for compression molding, the pressure is 120 tons, the mold temperature is 180°C, and the pressure is maintained for 30 minutes for curing; after the curing is completed, take out the mold, put it in cold water for cooling, open the mold, and take it out to obtain a blank with a density of 1.4g / cm 3 ;
[0137] S4, embryo body processing: machining the embryo body prepared in step S3 to obtain a carbon ceramic brake disc rough embryo, including removing burrs, processing heat dissipation holes on the disc surface, and processing side ventilation holes;
[0138] S5, carbonization: carbonizing the carbon ceramic brake disc blank prepared in step S4 in a carbonization furnace, with the maximum carbonization temperature being 1200° C. and the total carbonization time being 60 h, to obtain a carbonized blank;
[0139] S6, ceramicization: placing the carbide embryo prepared in step S5 in a siliconizing tool, brushing boron nitride powder on the surface of the tool, adding a piece of graphite paper between the tool and the carbide embryo, adding silicon particles on the upper and lower surfaces of the carbide embryo, the mass ratio of silicon particles to the carbide embryo is 1.5:1, and the mass ratio of silicon particles on the upper surface and the lower surface of the carbide embryo is 1:3, placing the tool and the embryo in a special siliconizing furnace, siliconizing at 1600°C~1700°C for 3 h~5 h, to obtain a ceramic embryo;
[0140] S7, finishing: polishing the disc surface of the ceramic embryo prepared in step S6, processing through holes and assembly holes, completing subsequent assembly and testing processes, and preparing a finished carbon ceramic disc.
[0141] Example 2
[0142] The method is basically the same as Example 1, except that in step S1, the mulling temperature is 65°C.
[0143] Example 3
[0144] The method is basically the same as Example 1, except that in step S1, the mulling temperature is 70°C.
[0145] Example 4
[0146] The method is basically the same as Example 1, except that in step S2, the mass ratio of the chopped carbon fiber to the intermediate mixture is 0.8:1.
[0147] Example 5
[0148] S1. Prepare binder asphalt, carbon powder, pore former (PVB) and metal oxide (aluminum oxide) in a mass ratio of 30:15:3:2, place the carbon powder, pore former and metal oxide in a kneader for preheating and kneading for 60 minutes, and the kneader temperature is 150°C; melt the asphalt at 160°C, add it into the kneader and knead until the paste temperature rises to 190°C, discharge the material, crush it into powder, and obtain an intermediate mixture;
[0149] S2, chopped carbon fiber (12K T700 grade sizing carbon fiber, the slurry is a PU solution with a solid content of 2% to 4%, and the length is 8 mm) and the intermediate mixture prepared in step S1 are mixed uniformly in a high-speed mixer at a mass ratio of 1:1, and the speed is 20 r / min at room temperature to obtain a carbon fiber mixture;
[0150] The carbon fiber mixture is subjected to compression molding, embryo body processing, carbonization, ceramicization and fine processing in sequence according to steps S3 to S7 of Example 1 to prepare a finished carbon ceramic disc.
[0151] Example 6
[0152] S1. Prepare a binder (liquid phenolic resin), carbon powder, pore-forming agent (PVB) and metal oxide in a mass ratio of 35:20:3:2, place the carbon powder, pore-forming agent and metal oxide in a kneader for preheating and kneading for 10 minutes at a kneader temperature of 70°C; add liquid phenolic resin and knead for 30 minutes, discharge the material, and obtain an intermediate mixture;
[0153] S2, chopped carbon fiber (12K T700 grade sizing carbon fiber, the slurry is a PU solution with a solid content of 2% to 4%, and the length is 8 mm) and the intermediate mixture prepared in step S1 are mixed uniformly in a high-speed mixer at a mass ratio of 1:1, the temperature is 120° C., and the speed is 20 rpm to obtain a carbon fiber mixture;
[0154] The carbon fiber mixture is subjected to compression molding, embryo body processing, carbonization, ceramicization and fine processing in sequence according to steps S3 to S7 of Example 1 to prepare a finished carbon ceramic disc.
[0155] Example 7
[0156] The process is basically the same as Example 5, except that in step S1, the kneading machine temperature is 120°C.
[0157] Comparative Example 1
[0158] The method is basically the same as Example 1, except that steps S1-S2 of Example 1 are replaced by the following steps:
[0159] Chopped carbon fiber (12K T700 grade sizing carbon fiber, the slurry is a PU solution with a solid content of 2% to 4%, and the length is 8 mm), a binder (solid phenolic resin), carbon powder, a pore-forming agent (PVB) and a metal oxide are uniformly mixed in a high-speed mixer according to a mass ratio of 50:25:20:3:2, and the speed is 20 r / min at room temperature to obtain a carbon fiber mixture;
[0160] The carbon fiber mixture is subjected to compression molding, embryo body processing, carbonization, ceramicization and fine processing in sequence according to steps S3 to S7 of Example 1 to prepare a finished carbon ceramic disc.
[0161] Comparative Example 2
[0162] The method is basically the same as Example 1, except that steps S1-S2 of Example 1 are replaced by the following steps:
[0163] Chopped carbon fiber (12K T700 grade sizing carbon fiber, the slurry is a PU solution with a solid content of 2% to 4%, and the length is 8mm), a binder (solid phenolic resin), carbon powder, a pore-forming agent (PVB) and a metal oxide are placed in an internal mixer in a mass ratio of 50:25:20:3:2, and the mixing temperature is 60°C, the speed is 10 r / min to 30 r / min, and the mixing temperature is higher than 85°C (about 15 min), and the material is discharged, and the material after the mixing is crushed to obtain a carbon fiber mixture;
[0164] The carbon fiber mixture is subjected to compression molding, embryo body processing, carbonization, ceramicization and fine processing in sequence according to steps S3 to S7 of Example 1 to prepare a finished carbon ceramic disc.
[0165] Comparative Example 3
[0166] The method is basically the same as Example 6, except that steps S1-S2 of Example 4 are replaced by the following steps:
[0167] Prepare chopped carbon fibers (12K T700 grade sizing carbon fibers, the slurry is a PU solution with a solid content of 2% to 4%, and the length is 8 mm) with a mass ratio of 60:35:20:3:2, a binder (liquid phenolic resin), carbon powder, a pore-forming agent, and a metal oxide, place the chopped carbon fibers, carbon powder, a pore-forming agent, and a metal oxide in a kneader and preheat and knead for 10 minutes at a kneader temperature of 70°C; add the liquid phenolic resin and knead for 30 minutes, and discharge the material to obtain a carbon fiber mixture;
[0168] The carbon fiber mixture is subjected to compression molding, embryo body processing, carbonization, ceramicization and fine processing in sequence according to steps S3 to S7 of Example 1 to prepare a finished carbon ceramic disc.
[0169] The metallographic image of the finished carbon ceramic disc prepared in Example 1 is as follows: Figure 1 As shown, the metallographic image of the finished carbon ceramic disc prepared in Example 5 is as follows Figure 2 As shown, the metallographic image of the finished carbon ceramic disc prepared in Example 6 is as follows Figure 3 As shown, the metallographic image of the finished carbon ceramic disc prepared in Comparative Example 1 is as follows Figure 4 As shown, the metallographic image of the finished carbon ceramic disc prepared in Comparative Example 2 is as follows Figure 5 As shown, the metallographic image of the finished carbon ceramic disc prepared in Comparative Example 3 is as follows Figure 6 shown.
[0170] Figure 1~Figure 3 The metallographic diagram of the carbon ceramic brake disc material displayed shows that the fiber bundles are relatively complete and are evenly distributed in the silicon carbide matrix. The material strength is relatively high. Figure 4 The fibers in the matrix are also relatively complete, but there are large chunks of silicon carbide without fiber reinforcement, and the bonding performance with the fibers is poor. Figure 5 , Figure 6 The fibers are evenly distributed in the silicon carbide matrix, but the fiber bundling is destroyed and the strength of the material is low.
[0171] The density and porosity of the finished carbon ceramic plate are measured by drainage method, and the density is required to be (2.2±0.1g / cm 3 ) and porosity (≤10%).
[0172] The tensile strength, bending strength, compressive strength and impact toughness of the samples were tested using an electronic universal testing machine;
[0173] Tensile strength specimen size (dumbbell specimen): 120mm*18mm*4mm;
[0174] Bending strength specimen size: 55mm*10mm*4mm;
[0175] Compression strength: 10mm*10mm*10 mm;
[0176] Impact toughness specimen size: 55mm*10mm*10mm.
[0177] Brake disc simulation bench test:
[0178] The JF122 series automobile brake inertia test bench of Jilin Jida Electromechanical Equipment Co., Ltd. was used to conduct a simulated braking test on the finished carbon ceramic disc of the embodiment; the experiment was conducted based on the SAE J2522 standard; this standard includes various performance tests on brake discs and is based on the structure, demonstration and partial definition of the current European AK Master test method version.
[0179] The test results are shown in Table 1.
[0180] Table 1
[0181]
[0182] As can be seen from Table 1, compared with the carbon ceramic disc prepared by the traditional preparation method (Comparative Example 1), the carbon ceramic discs prepared in each embodiment have significantly improved tensile strength, bending strength and impact toughness on the basis of ensuring density, porosity and friction coefficient, indicating that the present application first mixes carbon powder, metal oxide, binder and additives for smelting or kneading, and then mixes the prepared intermediate mixture with chopped carbon fibers, which can solve the problems of light and heavy powder stratification in the traditional mixing process and improve the bonding force between the chopped carbon fibers and the powder. In Comparative Examples 2 and 3, the chopped fibers and other components are directly smelted or kneaded at the same time, resulting in a significant decrease in tensile strength and impact toughness.
[0183] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0184] The above-described embodiments only express several implementation methods of the present application, which is convenient for understanding the technical solution of the present application in detail, but it cannot be understood as limiting the scope of protection of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several modifications and improvements can be made, which all belong to the scope of protection of the present application. It should be understood that the technical solutions obtained by those skilled in the art through logical analysis, reasoning or limited experiments on the basis of the technical solutions provided in the present application are all within the scope of protection of the claims attached to the present application. Therefore, the scope of protection of the patent of this application shall be based on the contents of the attached claims, and the description and drawings can be used to explain the contents of the claims.
Claims
1. A method for preparing a carbon ceramic product, characterized in that: The following steps are involved: The carbon powder, the metal oxide, the binder and the additive are mixed and kneaded to prepare an intermediate mixture; Mixing the chopped carbon fibers with the intermediate mixture to prepare a carbon fiber mixture; The carbon fiber mixture is subjected to molding treatment, carbonization treatment and siliconization treatment in sequence to prepare a carbon ceramic product.
2. The preparation method according to claim 1, characterized in that The temperature of the banburying is 60° C. to 80° C., and the time is 10 min to 30 min.
3. The preparation method according to claim 1, characterized in that: The kneading temperature is 120° C. to 150° C., and the kneading time is 30 min to 120 min.
4. The preparation method according to claim 1, characterized in that In the step of mixing the chopped carbon fibers with the intermediate mixture, the mixing temperature is 20° C. to 35° C., and the stirring speed is 10 r / min to 30 r / min.
5. The preparation method according to any one of claims 1 to 4, characterized in that The mass ratio of the binder, the carbon powder, the additive and the metal oxide is 25-35:10-30:3-5:0.5-2.
6. The preparation method according to any one of claims 1 to 4, characterized in that: The mass ratio of the chopped carbon fiber to the intermediate mixture is 0.5-1.5:
1.
7. The preparation method according to any one of claims 1 to 4, characterized in that: The preparation method meets at least one of the following characteristics: (1) The binder includes at least one of solid phenolic resin, asphalt and liquid resin; (2) The metal oxide includes at least one of aluminum oxide, yttrium oxide and zirconium oxide; (3) The additive includes a pore-forming agent.
8. The preparation method according to claim 7, characterized in that: The pore-forming agent includes at least one of ethylene glycol, PVB and plant fiber powder.
9. The preparation method according to any one of claims 1 to 4, characterized in that: The preparation method meets at least one of the following characteristics: (1) The temperature of the molding process is 120°C to 200°C, the pressure of the molding process is 100 to 150 tons, and the holding time of the molding process is 20 min to 40 min; (2) The temperature of the carbonization treatment is 1000°C to 1200°C, and the time of the carbonization treatment is 50 h to 70 h; (3) The temperature of the siliconizing treatment is 1500°C to 1700°C, and the time of the siliconizing treatment is 3 h to 6 h; (4) The siliconizing treatment includes: placing silicon sources on the upper surface and the lower surface of the carburized body after the carbonization treatment, respectively, and performing the siliconizing treatment in a siliconizing furnace.
10. The preparation method according to claim 9, characterized in that: The silicon source includes silicon alone.
11. A carbon ceramic product, characterized in that: The carbon ceramic product is prepared by the method for preparing the carbon ceramic product according to any one of claims 1 to 10.
12. The carbon ceramic product according to claim 11, characterized in that The carbon ceramic product comprises a carbon ceramic brake disc.
13. A means of transport, characterized in that: Comprising the carbon ceramic product as claimed in claim 11 or 12.
Citation Information
Patent Citations
Preparation method of carbon fiber-reinforced silicon carbide brake disc
CN113548902A
Preparation method of carbon-based porous material with stable, adjustable and uniform pore diameter
CN118405936A